A generalized computational approach to predict high-frequency acoustic pressure response of cavity structures for structural health monitoring of wind turbine blades. Issue 3 (June 2022) - Traylor, Caleb; Inalpolat, Murat
This paper details the development of a generalized computational approach that enables prediction of cavity-internal sound pressure distribution due to flow-generated noise at high frequencies. The outcomes of this research is of particular interest for development of an acoustics-based structural health monitoring system for wind turbine blades. The methodology builds from existing reduced-order aeroacoustic modeling techniques and ray tracing based geometrical acoustics and is demonstrated on the model NREL 5 MW wind turbine blade as a case study. The computational predictions demonstrated that damage could be successfully detected in the first half of the blade cavity near the root and that the change in frequency content may be indicative of the type of damage that has occurred. This study provides a foundation to analyze specific blades and likely damage cases for determining key factors of system design such as number and placement of sensors as well as for hardware selection.